PENGARUH INKUIRI TERBIMBING BERBANTUAN VIDEO TERHADAP HASIL BELAJAR IPA SISWA SD DITINJAU DARI EFIKASI DIRI - Suharni Sukara; Amalia Sapriati; Ucu Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research describes the science learning outcomes of elementary school students who have high self-effecacy learning using the guided inquiry method assisted by books. The research was conducted on grade elementary school students in four public elementary schools in Tambora District,West Jakarta. Data collection was crried out using self-efficacy instruments (questionnaires) and science learning outcomes instruments (tests). The research results show that students with high self-efficacy learn using the guided inquiry method with the help of videos, and student with low self-efficacy learn with the help of books. Students with high self-efficacy get higher results ompared to students with low self-efficacy.The conclusion is that learning science using the video-assisted guided inquiry method for students with high self-efficcy get higher science learning outcomes compared to student with low efficacy.